The Effect of Harvest Area, Rice Productivity, and Population Density on Food Security in NTT Province 2018-2023 - Safitri, Risa Anggi; Suhartono, Edy (Jambura Equilibrium Journal, 2025)
Food security is one of the main keys to realizing the welfare of the people in Indonesia. Currently, Indonesia is still experiencing serious food security problems, especially rice availability. Based on the Central Bureau of Statistics 2024, the highest level of insecurity across Indonesia is in East Nusa Tenggara Province, with a value of 14.68%. Meanwhile, the population in East Nusa Tenggara Province is quite large, with more than 5 million people. If the level of vulnerability is at the highest rank, it can be said that East Nusa Tenggara Province has very low food security. This study aims to analyze the effect of rice harvest area, rice productivity, and population density on food security in 21 districts and 1 city of East Nusa Tenggara Province from 2018 to 2023. This study uses secondary data in the form of panel data. The sample used in this study is data from 22 districts and cities in East Nusa Tenggara Province for 6 periods, with details, namely 22 x 6 = 132. This study found that simultaneously, the variables of rice harvest area, rice productivity, and population density in East Nusa Tenggara Province had a significant effect on food security. While partially obtaining results, namely the variable area of rice harvest and rice productivity, there is a significant effect on food security. The total population variable has no significant effect on food security.